A Case Study On Management Of PCOS With A Herbal Formulation - Gaiju, Laxmita; Kapil, Soni (International Research Journal of Ayurveda & Yoga, 2021)
Nowadays, in the name of urbanization, there is increase in sedentary lifestyle, eating disorders, excessive stress from work and study, excessive exercise or physical activities. Due to this, women have been suffering from menstrual abnormalities such as oligomenorrhea, anovulation, infertility, etc. All these disorders are found together under a condition known as polycystic ovarian syndrome. Polycystic ovarian syndrome is a condition of hormonal imbalance characterized by oligomenorrhea/anovulation, polycystic ovaries and clinical or biochemical hyperandrogenism. Any 2 of these 3 criteria are enough to define this condition. In Ayurveda, this condition is very much similar to conditions like Artava Kshaya (Oligomenorrhea), Pushpaghani Jatiharini (Anouvulatory cycle), Kaphaj-vataj Artavdushti (Hyperandrogenic condition). When not treated early, it leads to complications like glucose intolerance, dyslipidemia, cardiac disease, infertility. A 22 year old female of married life of 2 years presented to PTSR OPD of RGGPGA College and Hospital, Paprola, with the complaints of irregularity of menses with increased interval since about 5 and half years and inability to conceive since 2 years. Ultrasonographic findings showed Polycystic ovarian pattern. A Samshaman regimen, Nagaradi Kwath was planned for the management of oligomenorrhea which was the major symptom of the patient. The regimen included of composition of medicinal plants (ref. Harita Samhita) given as decoction orally. Soon after 6 months of intake of the Ayurvedic regimen along with practice of appropriate diet and Yogasana, menstrual pattern was established in natural way and the patient conceived on the 6th month of her treatment.